PEMANFAATAN MEDIA PEMBELAJARAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DI KELAS V SDN TAMAN BARU 1 CILEGON - Sa’adiyah, Sa’adiyah; Dayurni, Popi; Ismatullah, Ismatullah (Journal of Professional Elementary Education, 2025)
The use of Information and Communication Technology (ICT) in learning is an important need in the digital era to improve the quality of education. However, at the elementary school level, the application of ICT still faces challenges such as limited infrastructure and teacher competence. This study aims to describe the use of ICT-based learning media in grade V of SD Negeri Taman Baru 1 Cilegon. The research method used is a case study with a qualitative approach. Data were collected through interviews, observations, and documentation of grade V teachers. Data analysis was carried out descriptively to understand the extent to which ICT is utilized in the learning process. The results of the study indicate that the use of ICT-based learning media in SD Negeri Taman Baru 1 Cilegon has been quite optimal. Teachers use devices such as LCD projectors and the internet to deliver materials, which makes learning more interesting and increases student motivation. Students show high enthusiasm, are active in discussions, and are able to learn independently.